Evaluation of Microbial Recovery from Raw Materials for Pharmaceutical Use - Eissa, Mostafa; Mahmoud, Ahmed (Journal of Food and Pharmaceutical Sciences, 2016)
Microbiological quality of raw materials used in pharmaceutical manufacturing is critical attribute that affects the bioburden level of the final product. If the preliminary treatment for the microbiological analysis of the material is not suitable to recover actual microbial content, false estimation of microbial presence and/or count in raw materials may impact final product quality and safety. Accordingly a survey study was conducted on 12 selected materials that are used extensively in the manufacturing facility in order find suitable technique to recover low-level inoculums of standard strains. The basic processing and/or neutralization technique was dilution alone or in combination with chemical neutralization or less frequently filtration. Dill oil was the only raw material required combination of dilution and chemical neutralization for both of microbial enumeration and detection while this combination was necessary only in enumeration for Cetostearyl Alcohol. Although dilution method may be adopted alone for Sorbitol solution 70% yet filtration was done in combination to facilitate the visualization of commonly found yeast contaminant from the suppliers of the raw materials. Balsam Peru required the highest dilution among the tested materials for enumeration. The applied neutralization techniques were effective in detecting low level contamination in raw materials.